Synthesis and configurations of YF-0200R A and B. Issue 23 (9th June 2016) - Wang, Xiao-Dan; Xu, Ze-Jun; Zhu, Shijun; Wu, Yikang; Hou, Yan-Jun
Abstract: Two natural unsaturated fatty acids with aspargyl protease inhibition activity were synthesized for the first time. The stereogenic centers were installed by using Brown asymmetric allylation or chiral building blocks derived fromd -glucose, respectively. The conjugate diene unit was introduced via an HWE reaction. The geometry of the CC double bonds was clearly shown to be ( E ) by 1 H NMR in C6 D6 . The spectroscopic data for the synthetic samples were in excellent consistency with those reported for the corresponding natural ones. The optical rotations were also compatible with those for the natural ones. The absolute configurations for natural YF-0200R A and B thus could be reliably assigned as (8 S ) and (8 S, 10 S ), respectively. Graphical abstract: